Cleaning management practice of a public bus terminal : case study : Larkin Public Bus Terminal - 419744 Mary Kurien (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah ) - Universiti Teknologi Malaysia, 2007